Can online markets make trade more inclusive? - Andreas Lendle; Marcelo Olarreaga (Asian Development Bank Institute (ADBI), 2017)
Technology made available by online markets has significantly reduced the cost of entry into international markets for small and medium sized firms, who can now reach far away consumers and create global reputation as a seller at very low costs. Empirical evidence using data from eBay sellers shows that a large share of online firms exports, even though they are on average much smaller than traditional offline firms. We show that in a world where income inequality is driven by an uneven distribution of capital rents, online markets help to reduce income inequality by providing smaller firms access to international markets.
Keywords: F1; F6; 330; Online markets; international trade; income inequality